Evaluating the effect of a ducted winglet on the induced drag of wind turbine blade using CFD and Trefftz plane analysis - Jakub Vincalek (Engineering with Computers)
A novel patented ducted winglet design is compared, using numerical simulations, to an unmodified wing tip and a standard winglet in the context of a wind turbine blade. The aim of the ducted winglet is to reduce the induced drag. This reduction of induced drag, at the wing tip, would be particularly beneficial to wind turbine performance. Throughout the comparison, we explore the aerodynamic phenomena described in the patent which claim to explain how the ducted winglet reduces induced drag. The simulations were run using a CFD solver, FLITE3D, that has been thoroughly validated on industrial scale aerodynamic problems. A mesh convergence study was carried out to ensure that the results have sufficient numerical accuracy for a consistent ranking with respect to the lift-to-drag ratio. A Trefftz plane analysis is conducted to measure the effect of the duct on induced drag. To the best of our knowledge, this is the first time that such a ducted design is tested in this context and compared to a standard unmodified blade and winglet. We found that the ducted winglet has a higher lift-to-drag ratio than an unmodified wing tip, but lower than a non-ducted winglet. Despite this, there is clear evidence that the duct had a positive influence on the induced drag. Our results show that with future optimisation this ducted winglet may prove beneficial to wind turbine design.